Academic staff perceptions and the identification of critical success factors in a merger of two academic institutions - Stephen, David Ferguson (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2010.